A lead-free halide hybrid perovskite (TMHD)BiCl5 for ultraviolet photodetection. Issue 19 (9th August 2022) - Weng, Wen; Chen, Qin; Fan, Yipeng; Li, Zhou; Huang, Haizhou; Wu, Hongchun; Ji, Chengmin; Lin, Wenxiong
Abstract : Lead halide hybrid perovskites with a wide bandgap ( e.g., CH3 NH3 PbCl3 ) have gained tremendous attention in the field of ultraviolet (UV) photodetection due to their brilliant optoelectronic activity. Abstract : Lead halide hybrid perovskites with a wide bandgap ( e.g., CH3 NH3 PbCl3 ) have gained tremendous attention in the field of ultraviolet (UV) photodetection due to their brilliant optoelectronic activity. Although the environment-unfriendly nature of lead in these hybrids is unfavorable for their wide-scale application. Exploring lead-free halide hybrid semiconductors for high-performance ultraviolet photodetection is extremely important. In this work, a new broadband lead-free hybrid perovskite (TMHD)BiCl5 (TMHD = N, N, N, N -tetramethyl-1, 6-hexanediammonium) is successfully prepared through a facile solution process. A low trap density of 8.2 × 10 10 cm −3 and a high carrier mobility of 0.62 cm 2 V −1 s −1 contribute to the charge transport properties. Furthermore, lateral UV photodetectors based on high-quality lead-free (TMHD)BiCl5 single crystals are fabricated for the first time, which show considerable on/off current ratios (>10 3 ) and a prominent photoresponsivity (8.8 mA W −1 ) under 266 nm irradiation. We anticipate that this study will provide new inspiration for designing broadband lead-free hybrids for promising UV optoelectronic applications.